Human local and total heat losses in different temperature - Wang, L.; Yin, H.; Di, Y.; Liu, Y.; Liu, J. (Physiology & Behavior, 2016)
This study investigates the effects of operative temperature on the local and total heat losses, and the relationship between the heat loss and thermal sensation. 10 local parts of head, neck, chest, abdomen, upper arm, forearm, hand, thigh, leg and foot are selected. In all these parts, convection, radiation, evaporation, respiration, conduction and diffusion heat losses are analyzed when operative temperature is 23, 28, 33 and 37 °C. The local heat losses show that the radiation and convection heat losses are mainly affected by the area of local body, and the heat loss of the thigh is the most in the ten parts. The evaporation heat loss is mainly affected by the distribution of sweat gland, and the heat loss of the chest is the most. The total heat loss of the local body shows that in low temperature, the thigh, leg and chest have much heat loss, while in high temperature, the chest, abdomen, thigh and head have great heat loss, which are useful for clothing design. The heat losses of the whole body show that as the operative temperature increases, the radiation and convection heat losses decrease, the heat losses of conduction, respiration, and diffusion are almost constant, and the evaporation heat loss increases. By comparison, the heat loss ratios of the radiation, convection and sweat evaporation, are in agreement with the previous researches. At last, the formula about the heat loss ratio of convection and radiation is derived. It's useful for thermal comfort evaluation and HVAC (heating, ventilation and air conditioning) design.